CLINICAL AND MORPHOLOGICAL FEATURES OF CHRONIC HEPATITIS C IN YOUNG CHILDREN - S. V. Chuelov; E. A. Leybman; T. V. Cherednychenko; A. L. Rossina; L. I. Nikolaeva; E. I. Samokhvalov (LLC "Diagnostics and Vaccines", 2015)
The research presents the analysis of the factors of macro-and microorganism facilitating the formation of liver cirrhosis (LC) in CHC in children. 20 patients with liver cirhossis of hepatitis C virus etiology have been observed. No reliable correlation between such factors as sex, age, route of infection, previous and concomitant diseases, genotype of the pathogen, duration of the infection has been discovered. The clinical, biochemical and ultrasound characteristics of liver cirrhosis of HCV-etiology in children have been presented. The changes of the frequency of occurrence of certain subtypes of the virus and the prevailing route of HCV-infection in recent years have been shown.